Elaboration of pork burger added with prebiotics as a fat substitute - Castro, Gabriel Beserra de; Castro, Janevane Silva de; Bitu, Luiz Alves; Maia, Mayra Garcia; Andrade, Ana Paula Colares de (Nutrivisa Revista de Nutrição e Vigilância em Saúde, 2025)
This study aimed to create pork burgers with polydextrose, developing three formulations: F1 (10% fat), F2 (10% fiber), and F3 (15% fiber). The centesimal composition, oxidative stability (pH, TBARS, color), and water retention capacity (WHC) were evaluated over 120 days of storage. All formulations had 19% protein, with F2 and F3 having the lowest lipid content (1.8% and 1.9%, respectively). pH values remained between 5.36 and 5.50. No lipid oxidation occurred in the polydextrose formulations during the first 60 days. The red color (a*) decreased, indicating myoglobin oxidation. F1 experienced greater water loss (7.9%), while F2 and F3 lost only 3.9%. The study concluded that polydextrose can replace fat in the product, reduce lipid oxidation, and improve yield and quality